Bivališča »krivopet«: Lokacije in mikrotoponimi Residences of the “Krivopete”: Locations and Microtoponyms - Barbara Ivančič Kutin (Studia Mythologica Slavica, 2016)
Krivopete are wild women whose feet are turned backwards. Folklore tradition about these mythical beings can be found in the extreme north-western part of the Slovenian ethnic territory: in Trenta, Breginj, Livško, and the Natissone Valleys in the Italian Slavia Veneta. Since folktales about the krivopete are typically installed in a concrete location these places have been identified through the toponyms and microtoponyms where the krivopete allegedly lived, manifested themselves, or acted. The number of locations and their position in space indicates in which (micro)locations this tradition was particularly strong. A common feature of such locations, which indicated where these women dwelled, was the hideous, inaccessible, and/or dangerous terrain: caves, rocky shelters, steep ravines, and streams.